ANALISIS PERBANDINGAN UNJUK KERJA WIND TURBINE TSD-500 DAN GH – 0.5K DI PILOT SMART GRID TEKNIK ELEKTRO UNIVERSITAS UDAYANA - I. W. Dhanan Arieyasa; Cok. G. Indra Partha; I. W. Sukerayasa (Program Studi Teknik Elektro UNUD, 2020)
Wind power generation is a power plant that converts kinetic energy into electrical energy by utilizing wind as its energy source. The Smart Grid Pilot Project in Microgrid, Udayana University's Electrical Engineering Study Program has a wind power plant for research. The wind power plants in the Smart Grid Pilot Project in Microgrid Udayana University's Electrical Engineering Study Program totaled 10 turbines with rated power of 500 Watt each, from 10 wind turbines there are 8 wind turbines with TSD-500 models made in Indonesia and 2 wind turbines with GH-0.5K models made in China. The data logger contained in the Pilot Smart Grind in Electrical Engineering, Udayana University, logs 10 wind turbines at a time, so the output power of each wind turbine is unknown. Performance analysis of wind turbine TDS-500 and GH-0.5K using a measuring instrument based on the ATmega 328 microcontroller so that it can find out which wind turbine is larger which results in better power output and performance. The results of this study indicate that the TSD-500 wind turbine performance is better than the GH-0.5K wind turbine.